PEMANFAATAN KECERDASAN BUATAN (AI) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM INOVASI, TANTANGAN, DAN DAMPAKNYA TERHADAP PEMAHAMAN KEAGAMAAN : PEMANFAATAN KECERDASAN BUATAN (AI) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM INOVASI, TANTANGAN, DAN DAMPAKNYA TERHADAP PEMAHAMAN KEAGAMAAN - Agus Jatmiko; Hikma Apriyani; Ilham Jaya Kesuma; Yuli Yanti; Muhammad Izzad Khairi Yazid; Meriyati; Chairul Amriyah (LP2M IAIN Sultan Amai Gorontalo, 2025)
The utilization of artificial intelligence (AI) in Islamic Religious Education (PAI) learning has become a promising innovation in enhancing students' religious understanding in the digital era. This research aims to explore how AI is used in PAI learning, the challenges faced in its implementation, and its impact on students' religious understanding. This research uses a qualitative approach with a literature study method and descriptive analysis of various studies and practices that have been implemented in technology-based Islamic education. The research results show that AI can provide a more interactive, adaptive, and personalized learning experience according to students' needs. However, there are several challenges that need to be addressed, such as dependence on technology, lack of understanding of ethics in the use of AI, and limitations in adapting learning content to Islamic values. Although there are positive impacts such as the increased understanding of religious concepts through interactive media, we must also be wary of the risk of reduced direct interaction between teachers and students. This can affect the affective aspect of Islamic Religious Education (PAI) learning. Therefore, the use of AI in Islamic Religious Education (PAI) must be balanced with appropriate policies, so that it remains in line with Islamic values and provides maximum benefits for students.